Adoption of digital tools in the context of the COVID-19 pandemic in the Region of the Americas - the Go.Data experience - Cristina Valencia; Giovanna Jaramillo-Gutierrez; Analía Rearte; Paula Rosin; Fernando Gassino; Silvia Edith Morreale; Lorena Gobern; Antonio Paredes; Marc Rondy; Evelyn Balsells; Pablo Galindo; Liz Parra; et al. (The Lancet Regional Health. Americas, 2022)
Summary: The COVID-19 pandemic has accelerated the growth of digital health tools. Although a number of different tools exist to support field data collection in the context of outbreak response, they have not been sufficient. This prompted the World Health Organization (WHO) to collaborate with the Global Outbreak Alert and Response Network (GOARN) and GOARN partners to develop a comprehensive system, Go.Data. Go.Data, a digital tool for outbreak response has simplified how countries operationalize and monitor case and contact data. Since the start of the pandemic, WHO and GOARN partners have provided support to Go.Data projects in 65 countries and territories, yet the demand by countries to have documented success cases of Go.Data implementations continues to grow. This viewpoint documents the successful Go.Data implementation frameworks in two countries, Argentina and Guatemala and an academic institution, the University of Texas at Austin.